Islam in the Digital Age - Karim H. Karim (International Institute of Islamic Thought, 2004)
This is Gary Bunt’s second monograph on the Muslims’ use of the Internet, the first being Virtually Islamic (Cardiff, UK: The University of Wales Press: 2000). It is a good contribution to the growing literature, and will appeal to students of contemporary Muslim societies and the sociocultural and religious influence of new communication technologies. The book provides a useful list of websites containing information on Islam and Muslims. Bunt suggests that a substantial number of Muslims use the Internet as a propagation and networking tool, to dialogue with each other, and to conduct research. For some, it is an important way to bypass state censorship and access other media, and it acts as a means of local and global contact. The Internet is used to disseminate and obtain decisions and points of interpretation on current events, and, for some individuals who are relatively unknown or treated as pariahs locally, to achieve fame in the larger ummah. Since September 2001, Muslims’ activities and activism on the Internet have proliferated; meanwhile, those in power have increased attempts to restrict them. There has been an increase in websites, chat rooms, and e-mail lists. The author justifies linking Muslims’ uses of the Internet with jihad and fatwas by stating that these two areas have seen the most significant integration of electronic activity with religion. However, he shuns alarmism about the Internet and Islam by presenting a rational analysis and discussion. Bunt admits that a small, albeit growing, minority in Muslim-majority countries uses information and communication technologies. Muslim online discourses are part of the contemporary discussion about Islamic identities. The Internet “has not superseded traditional forms of political expression, but is a means through which conventional boundaries and barriers can be transcended” (p. 11).